ENGLISH TEACHERS’ REFLECTIVE THINKING PRACTICE DURING THE ONLINE LEARNING AT SMAN 2 SINGARAJA - I Wayan Sastra Oka Paramartha; I Putu Ngurah Wage Myartawan; Ni Putu Astiti Pratiwi (Acitya: Journal of Teaching and Education, 2021)
The new learning system that is published by the Indonesian government as a prevention due to Covid-19 brings a new challenge for the teachers particularly in implementing 21st century learning. Teachers are suggested to do a reflection toward the online learning that has been conducted to find out the teaching and learning process quality. This study is aimed at investigating the level of teachers’ reflective thinking in which it was conducted in SMAN 2 Singaraja. There were two teachers involved in this study and the data were collected through the spreading of questionnaire and interview. The data were analyzed by using interactive data analysis to check the validity and reliability. The results showed that the awareness of the teacher in carrying out a process of reflection on learning during the online learning period. The efforts made by the English teacher at SMA N 2 Singaraja in improving the quality of learning both by discussing and innovating need to be used as an example for other teachers. In the future, of course, it is hoped that a better online learning process and learning objectives can be maximally achieved